Improvement of biomolecular analysis in thin films using in situ matrix enhanced secondary ion mass spectrometry. Issue 21 (27th September 2021) - Moshkunov, Konstantin; Tomasetti, Benjamin; Daphnis, Thomas; Delmez, Vincent; Vanvarenberg, Kevin; Préat, Véronique; Lorenz, Matthias; Quanico, Jusal; Baggerman, Geert; Lemiere, Filip; Dupont, Christine; Delcorte, Arnaud
Abstract : In situ matrix-enhanced SIMS provides sensitivity improvement for bio-sample molecular analysis and imaging. Abstract : Sensitivity to molecular ions remains a limiting factor for high resolution imaging mass spectrometry of organic and biological materials. Here, we investigate a variant of matrix-enhanced secondary ion mass spectrometry in which the transfer of matrix molecules to the analyte sample is carried out in situ ( in situ ME-SIMS). This approach is therefore compatible with both 2D and 3D imaging by SIMS. In this exploratory study, nanoscale matrix layers were sputter-transferred inside our time-of-flight (ToF)-SIMS to a series of thin films of biomolecules (proteins, sugars, lipids) adsorbed on silicon, and the resulting layers were analyzed and depth-profiled. For this purpose, matrix molecules were desorbed from a coated target (obtained by drop-casting or sublimation) using 10 keV Ar3000 + ion beam sputtering, followed by redeposition on a collector carrying the sample to be analyzed. After evaluating the quality of the transfer of six different matrices on bare Si collectors, α-cyano-4-hydroxycinnamic acid (CHCA) was selected for further experiments. The mass spectra and depth profiles obtained from the organic layer prior to and after the sputter-transfer of CHCA were compared, along with those obtained from regular ME-SIMS samples (dried droplets) and, finally, with MALDI data for the same matrix–analyte combinations. Signal amplification factors were calculated by dividing the integrated molecular intensities obtained with or without matrix transfer. While the amplification factors are between 0.5 and 2 for molecules already detected with high intensities in SIMS, such as cholesterol or human angiotensin, other compounds show very large integrated signal amplification, even above two orders of magnitude. This is the case for d -glucose and cardiolipin, for which the molecular ion intensity is low (or very low) under normal SIMS analysis conditions. For such low ionization probability compounds, the beneficial effect of the matrix is unquestionable. Test experiments on mouse brain tissue sections also indicate signal enhancement with the matrix, especially for high mass lipid ions.